THE EFFECT OF FINANCIAL COMPENSATION AND NON FINANCIAL COMPENSATION ON THE PERFORMANCE OF NON ASN EMPLOYEES AT THE DISTRICT OFFICE IN PALU CITY WITH WORK MOTIVATION AS AN INTERVENING VARIABLE - Apriliati, Rulya; Natsir, Syahir; Fadjar, Adfiyani (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
This study looks at the sub-district office in Palu City and how non-ASN employees' performance is impacted by monetary and non-monetary compensation. As a moderating variable, intrinsic motivation at work is important. In order to gather data, we distributed surveys to individuals who were not ASN employees at the Palu City District Head Office. With 88 participants, the sample was selected using a non-probability sampling method based on the Slovin formula. This study found that (1) non-ASN workers at Palu City's Subdistrict Office were significantly and positively impacted by financial remuneration. (2) Employees who are not ASNs at the Palu City Subdistrict Office have shown that non-monetary reward significantly improves their performance. (3) Not only that, but research at the Palu City sub-district office found that monetary incentives significantly and favorably affected the motivation of non-ASN personnel to do their jobs. (4) Moreover, staff at the Palu City sub-district office who are not ASNs are more motivated to work when they get non-monetary remuneration. (5) Employees who are not ASNs at the Palu City Subdistrict Office have shown that intrinsic drive at work significantly improves their productivity. (6) Additionally, it has been shown that monetary incentive significantly and positively affects performance by motivating the work of non-ASN staff at the Palu City Subdistrict Office. (7) In addition, research conducted at the Subdistrict Office in Palu City found that non-monetary incentive significantly improves performance by motivating non-ASN personnel to work hard.